2015
DOI: 10.1097/qad.0000000000000760
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renal tubular dysfunction on bone in tenofovir-exposed HIV-positive patients

Abstract: In HIV-positive patients receiving TDF-containing antiretroviral therapy, RTD was associated with lower BMD of the spine in HIV-positive men. RBPCR quantification may identify patients at increased risk of TDF-associated BMD loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…We observed a significantly higher prevalence of bone disease in patients with signs of KTD when compared with patients without KTD (54,8 vs 27,6%; p = 0.002 ) and a strong association between bone disease an KTD was also confirmed in the multivariable analysis. As previously described in HIV positive patients treated with TDF a strong association was observed between KTD and a lower bone mineral density [21, 22]. In addition the prevalence of bone disease (osteopenia/osteoporosis) such as the prevalence of KTD was similar to previous report by Calmy et al [23].…”
Section: Discussionsupporting
confidence: 88%
“…We observed a significantly higher prevalence of bone disease in patients with signs of KTD when compared with patients without KTD (54,8 vs 27,6%; p = 0.002 ) and a strong association between bone disease an KTD was also confirmed in the multivariable analysis. As previously described in HIV positive patients treated with TDF a strong association was observed between KTD and a lower bone mineral density [21, 22]. In addition the prevalence of bone disease (osteopenia/osteoporosis) such as the prevalence of KTD was similar to previous report by Calmy et al [23].…”
Section: Discussionsupporting
confidence: 88%
“…Pregnancy and exposure to exogenous estrogen are associated with significant increases DBP levels [21]. DBP levels are lowered in the setting of chronic liver disease due to decreased synthesis of DBP, chronic kidney disease due to increased renal losses, and in type 1 diabetes mellitus [22-4]. A few studies have found that DBP levels are decreased among adults and children in acute inflammatory states such as critical illness, sepsis, or following surgery, possibly due to increased urinary losses of DBP or increased actin binding to protect against polymerization of actin released from damaged tissue [25-7].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms underlying these associations remain unclear. Proposed mechanisms for these changes include toxicity of the proximal renal tubular cells causing urinary phosphate wasting, alterations of calcium and phosphate homeostasis, and osteomalacia [3,4]. However cases of Fanconi’s syndrome are rare and osteomalacia from clinically significant hypophosphatemia is relatively uncommon among patients receiving TDF, and does not seem to sufficiently account for the degree of bone loss and fracture reported [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The nucleotide reverse transcriptase inhibitor (NRTI) tenofovir disoproxil fumarate (TDF) has been linked with increased PTH levels, phosphate wasting by the kidney and low BMD in treated HIV-infected patients(4851), but there is no direct evidence that this occurs through alterations in vitamin D metabolism. However, vitamin D status may modify the effect of TDF on PTH levels(48, 52) and on BMD(47*).…”
Section: Vitamin D Deficiency In Hivmentioning
confidence: 99%